Pengaruh Pemberian Aromaterapi terhadap Kecemasan Hospitalisasi pada Anak - Azizah, Lina Wati Nur; Irdawati, Irdawati; Putri, Rosalia Dian Arsita (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Hospitalization is a crisis condition that requires sick children to undergo treatment. Children's anxiety responses during hospitalization mostly fall into three categories, namely a crying response when their parents leave them even for a short time, rebellion when given medical therapy, and refusal when an injection is given. Aromatherapy can stimulate the parasympathetic system, which can help reduce blood pressure and anxiety levels. To determine the effect of giving aromatherapy to reduce anxiety in children who are hospitalized. This case study uses a nursing care approach by applying aromatherapy therapy for 15 minutes given to five preschool-aged children who experienced anxiety due to hospitalization as measured using the Visual Anxiety Scale (VAS). Providing an aromatherapy intervention had an effect on reducing the anxiety scale in pre-school-aged children due to hospitalization. Conclusion: The intervention of giving aromatherapy for 15 minutes can reduce anxiety in children undergoing hospitalization. Keywords: Aromatherapy, Anxiety, Hospitalization, Children  ABSTRAK Hospitalisasi merupakan kondisi krisis yang mengharuskan anak sakit untuk menjalani perawatan. Respon kecemasan anak saat hospitalisasi paling banyak menunjukkan pada tiga kategori, yaitu respon menangis saat ditinggal orang tua walaupun dalam waktu singkat, memberontak saat diberikan terapi pengobatan, dan penolakan saat akan dilakukan injeksi. Aromaterapi dapat merangsang system parasimpatis yang dapat membantu mengurangi tekanan darah dan menurunkan tingkat kecemasan. Mengetahui pengaruh pemberian aromaterapi untuk mengurangis kecemasan pada anak yang mengalami hospitalisasi. Studi kasus ini menggunakan  pendekatan asuhan keperawatan dengan menerapkan terapi pemberian aromaterapi selama 15 menit yang diberikan pada lima anak usia prasekolah yang mengalami kecemasan akibat hospitalisasi yang diukur menggunakan Visual Anxiety Scale (VAS). Pemberian intervensi aromaterapi memberi pengaruh terhadap penurunan skala kecemasan pada anak usia pra sekolah akibat hospitalisasi. Intervensi pemberian aromaterapi selama 15 menit dapat menurunkan kecemasan pada anak  yang menjalani hospitalisasi. Kata Kunci: Aromaterapi, Kecemasan, Hospitalisasi, Anak